ESG reporting: ethical concerns for tourism industry - Mohd Zailanee, Nur Fatihah Najwa; Nik Wan, Nik Zam (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Tourism industry offers a broad range of services including hospitality, transportation, food and beverage, and entertainment. To protect Malaysia's natural and cultural resources the industry is increasingly required to adopt sustainable practices. By focusing on ESG concepts, tourism businesses can reduce their environmental footprint, generate positive social outcomes, and enhance their governance practices. ESG reporting is the mechanism usable to convey their practices publicly. However, in preparing ESG reporting, tourism industry might face several conflicts such as conflict of interest between stakeholders who might demand different requirement. They also in dilemma to balance between transparency dan confidentiality. A pursuit of important financial gains often conflicts with sustainable business practices, leading to decisions that undermine environmental and social responsibility. To mitigate the risk of such conflicts clear policies are necessary and regular reviews and training are recommended. Integration of ESG into tourism is important toward sustainability and responsibility in the tourism industry. The tourism industry nowadays must adapt to meet those expectations as environmental and social awareness grows.